2013
DOI: 10.3892/or.2013.2240
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Src enhances the cytotoxic effect of temozolomide through AKT in glioma

Abstract: Abstract. Src is an attractive target since it is overexpressed in a number of malignancies, including glioma. However, the mechanism of Src signaling as well as its silencing effect on temozolomide in glioma is not well known. We hypothesized that downregulation of Src may enhance the cytotoxic effect of temozolomide on glioma. As expected, Src was overexpressed in glioblastoma multiforme (GBM) compared with normal brain tissues. Src silencing suppressed tumor proliferation and induced apoptosis in glioma. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…Thus, we further analyzed which signaling pathways and apoptotic factors are altered upon integrin silencing. Our data revealed that integrin αVβ3 transmits signals through pFAK, pSrc and pAkt, which is in line with results showing that Src silencing enhanced the cytotoxic effect of TMZ in LN229 cells [44]. The same inhibition of FAK/Src/Akt in glioma cells was also shown upon CGT [45].…”
Section: Discussionsupporting
confidence: 89%
“…Thus, we further analyzed which signaling pathways and apoptotic factors are altered upon integrin silencing. Our data revealed that integrin αVβ3 transmits signals through pFAK, pSrc and pAkt, which is in line with results showing that Src silencing enhanced the cytotoxic effect of TMZ in LN229 cells [44]. The same inhibition of FAK/Src/Akt in glioma cells was also shown upon CGT [45].…”
Section: Discussionsupporting
confidence: 89%
“…27 Alterations to MGMT levels or mismatch repair status have been proposed as the main drivers for the development of this resistance, 13 but activation of the Akt pathway has also been proposed and linked with Src levels. 45 A study by Sun et al 41 showed that TMZ-resistant glioma cells were associated with changes in actin cytoskeleton-related proteins and increased adhesion and migration properties that are known to be functionally linked to invadopodia-associated mechanisms. Therefore, the involvement of the EGFR-Src-(PI3)/AKT pathway in glioma invasion, invadopodia formation/activity, and treatment resistance (radiotherapy/TMZ) highlights the potential importance of this signaling axis as a therapeutic avenue in targeting glioma invasion through invadopodia after radiotherapy and TMZ treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The Cx43 C-terminus interacts with a number of signaling molecules including c-Src, protein kinase C, AKT serine/threonine kinase, and mitogen-activated protein kinase to name a few (reviewed in [63 • ]). These interactions can also affect the phosphorylation status of Cx43 and consequently regulate its degradation, subcellular localization, and channel assembly processes, in addition to potentially mediating GBM resistance to TMZ [64,65]. Independent of channel activity, we have also found that aCT1 sensitizes GBM to TMZ in association with suppression of AKT activity [6 •• ].…”
Section: Therapeutic Opportunity For Connexin43 Peptidomimeticsmentioning
confidence: 99%